2019
DOI: 10.1088/1742-6596/1400/6/066045
|View full text |Cite
|
Sign up to set email alerts
|

High-power 0.98 µm range diode lasers based on InGaAs/GaAs quantum well-dot active region

Abstract: We present a study of characteristics of the edge-emitting lasers operating in the 0.98 μm wavelength range and based on a new type of InGaAs/GaAs active region – quantum well-dots (QWD). Utilizing the QWD active region in broadened 1.3 μm waveguide (BWG) allowed us to decrease the internal loss down to 0.5 cm−1 and to demonstrate the maximum output power of 13W and 50W in continuous wave (CW) and pulse operation regimes respectively. The investigation of the lasing spectra under high pulse injection currents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…It was demonstrated that QWDs are similar to quantum dots in that up to 20 QWD layers [5] may be grown in an active region without dislocations due to a drop in elastic stresses. This stress relaxation also allows one to expand a waveguide, thus providing the needed modal gain for high-power lasers [6]. An optical gain of 33 cm −1 in a single QWD layer, which is much higher than the corresponding value for QDs and comparable to the one for QWs, was demonstrated experimentally [7].…”
Section: Introductionmentioning
confidence: 98%
“…It was demonstrated that QWDs are similar to quantum dots in that up to 20 QWD layers [5] may be grown in an active region without dislocations due to a drop in elastic stresses. This stress relaxation also allows one to expand a waveguide, thus providing the needed modal gain for high-power lasers [6]. An optical gain of 33 cm −1 in a single QWD layer, which is much higher than the corresponding value for QDs and comparable to the one for QWs, was demonstrated experimentally [7].…”
Section: Introductionmentioning
confidence: 98%
“…Было показано, что аналогично квантовым точкам за счет уменьшения упругих напряжений в активной области можно выращивать вплоть 20 слоев КЯТ [5] без образования дислокаций. Снижение напряжений позволяет также расширить волновод, что дает возможность обеспечить необходимое модальное усиление в лазерах высокой мощности [6]. Для одного слоя КЯТ экспериментально продемонстрировано оптическое усиление 33 см −1 [7], что значительно превосходит значения для КТ и сопоставимо с КЯ.…”
Section: Introductionunclassified